Sustainable mobility in auto-dominated Metro Boston: Challenges and opportunities post-COVID-19 - Basu, Rounaq; Ferreira, Joseph (Transport policy, 2021)
The COVID-19 pandemic has disrupted society as we knew it in a variety of ways, with especially severe impacts on low-income households. Even before COVID-19, Metro Boston was witnessing a rise in private car ownership and decreasing mass transit ridership, further exacerbated by a historical spatial mismatch that made low-income commuters relatively more dependent on mass transit. Accounts of overcrowded buses and trains since early March have heightened psychological dread among regular transit commuters, some of whom have already purchased a private car or intend to do so within the next year. Uncertainty around transit service frequency and erosion of trust in the MBTA are the primary challenges for rebuilding transit rider confidence, which is likely to be a long and slow process. Low transit ridership levels can lead to fiscal challenges on the horizon and consequent service cuts, which necessitate the need for adopting a multi-modal approach to affordable and sustainable urban mobility. A narrow window is available to discourage a further shift to cars that will further cannibalize transit. Given the diversity of mobility services available in Metro Boston, designing a MaaS pilot with close attention to technological integration and cost salience can be crucial in showcasing the value of multi-modal and cross-modal accessibility. Such programs must be synergistic with concurrent transit service improvements and car-commute disincentives, such as in-town parking charges and road-use charges, without impeding access to affordable mobility for low-income and essential workers. Looking at the various agile policy responses of several cities in Metro Boston over the last few months, we are cautiously optimistic that sustainable mobility will become a major theme in urban and regional mobility policies in the post-COVID recovery period. •Metro Boston was witnessing increasing car ownership and decreasing transit ridership pre-COVID.•After COVID-19, transit service uncertainty and fear of overcrowding have led to erosion of trust in the MBTA.•18% of zero-car households intend to purchase a car because of COVID-19, 26% among them within the next year.•ICT-enabled mobility services can motivate MaaS programs, but cost salience and multi-stakeholder coordination are key challenges.•Car-commuting disincentives and transit-centered multi-modal programs are both necessary for post-COVID sustainable mobility.